The Bank for International Settlements - Smith, Jeremiah (Quarterly Journal of Economics, 1929)
Public interest in the Bank, 713. — Reasons for its establishment, 714. — Gradual development of the idea, 715. — Need of international financial cooperation, 716. — Structure of the Bank, 717. — Powers of the Bank, 721. — Size of the Bank, 721. — Conclusions: The Bank has two functions, primary and auxiliary, 723. — Impossibility of predicting what may be expected from the latter, 724.